New 3,3’-((4-Aryl) methylene)bis(4-hydroxy-2H chromen 2- one) (MHO) derivatives as Corrosion Inhibitor - Al-Majedy, Yasameen K.; Ibraheem, Hiba H.; jasem, Ali; Al-Amiery, Ahmed A. (Journal of Petroleum Research and Studies, 2020)
New green natural particles as corrosion inhibitor namely, macromolecules were incorporated beginning from 4-hydroxycoumarin with 4-nitrobenzaldehyde in the presence of glacial acid (1) then synthesis with methyl bromoacetate after that this compound (2) used to synthesis of 2,2’-(3,3’-((4-nitrophenyl)methylene)bis(2-oxo-2H-chromene-4,3 diyl))bis(oxy)diacetohydrazide (3) when was refluxed with hydrazine hydrate when compound(2) refluxed with HCl to obtain compound (4) and tested all the synthesis compounds on mild steel (MS) in 1 M HCl, 1M H2SO4 media by a weight loss method and identification of the surface technique employee scanning/electron/microscope (SEM) studies. The weight loss investigation demonstrated that inhibition performances have been improved via concentration raising of inhibitor. To support our results scanning electron microscopy was employed to clarify the surface of the MS with and without synthesis compounds in 1.0 M HCl and1.0M H2SO4 media.